2016
DOI: 10.1371/journal.pgen.1005872
|View full text |Cite
|
Sign up to set email alerts
|

The SMC-5/6 Complex and the HIM-6 (BLM) Helicase Synergistically Promote Meiotic Recombination Intermediate Processing and Chromosome Maturation during Caenorhabditis elegans Meiosis

Abstract: Meiotic recombination is essential for the repair of programmed double strand breaks (DSBs) to generate crossovers (COs) during meiosis. The efficient processing of meiotic recombination intermediates not only needs various resolvases but also requires proper meiotic chromosome structure. The Smc5/6 complex belongs to the structural maintenance of chromosome (SMC) family and is closely related to cohesin and condensin. Although the Smc5/6 complex has been implicated in the processing of recombination intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 94 publications
5
44
1
Order By: Relevance
“…SMC5/6 was also visible along chromosome axes at pachynema in oocytes, which was also detected in mouse spermatocytes (Gomez et al, 2013). In addition, transient foci of SMC6 were detected along the chromosome arms in female germ cells during pachynema, suggesting a role during meiotic recombination, which has previously been reported using budding yeast and Caenorhabditis elegans (Bickel et al, 2010;Hong et al, 2016;Checchi et al, 2014;Copsey et al, 2013;Lilienthal et al, 2013;Xaver et al, 2013). In mammals, every chromosome pair obtains many recombination sites but generally yields only one to two crossover sites (Kauppi et al, 2004).…”
Section: Smc5/6 Localization Pattern Implicates Multiple Functions Dusupporting
confidence: 65%
See 1 more Smart Citation
“…SMC5/6 was also visible along chromosome axes at pachynema in oocytes, which was also detected in mouse spermatocytes (Gomez et al, 2013). In addition, transient foci of SMC6 were detected along the chromosome arms in female germ cells during pachynema, suggesting a role during meiotic recombination, which has previously been reported using budding yeast and Caenorhabditis elegans (Bickel et al, 2010;Hong et al, 2016;Checchi et al, 2014;Copsey et al, 2013;Lilienthal et al, 2013;Xaver et al, 2013). In mammals, every chromosome pair obtains many recombination sites but generally yields only one to two crossover sites (Kauppi et al, 2004).…”
Section: Smc5/6 Localization Pattern Implicates Multiple Functions Dusupporting
confidence: 65%
“…Abnormal condensin localization was also observed using Smc5 cKO mouse embryonic stem cells (Pryzhkova and Jordan, 2016). Furthermore, mutation of smc-5 in C. elegans leads to abnormal distribution of condensin along bivalents during meiosis I (Hong et al, 2016). However, previous studies were not able to determine whether the defects in condensin localization were specific to the prophase to metaphase transition.…”
Section: Smc5 Is a Maternal-effect Genementioning
confidence: 96%
“…SMC5/6 seems to be involved in double-strand break (DSB) repair as it is enriched at DSB sites in budding yeast and C. elegans [12,14,16]; it localizes side by side with RAD51 in budding yeast and humans [9,12,16] and its deletion results in an increase in RAD51 foci and chromosome fragmentation in C. elegans [14]. Furthermore, Smc5/6 has been found to play a role in the resolution of meiotic recombination intermediates and mutations of Smc5, Smc6 or the SUMO ligase domain of Nse2 lead to the accumulation of toxic joint molecules in yeast and C. elegans [12,15,16,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Alteration in crossover distribution in the brc-1 mutant may result from changes in the chromatin landscape, which has been linked to BRCA1 function in mammals (BROERING et al 2014;DENSHAM et al 2016), and has been shown to alter crossover patterning (MEZARD et al 2015;YU et al 2016). A surprising number of C. elegans meiotic mutants display altered crossover distribution (ZETKA AND ROSE 1995;MENEELY et al 2012;SAITO et al 2012;SAITO et al 2013;WAGNER et al 2010;CHUNG et al 2015;HONG et al 2016;JAGUT et al 2016;Janisiw et al 2020). While the underlying mechanisms are not clear, it may be a consequence of altering the use of crossover versus non-crossover pathways within a particular chromatin environment as suggested by Saito and Colaiacovo (SAITO AND COLAIACOVO 2017).…”
Section: Brc-1-brd-1 Function When Male Meiosis Is Perturbedmentioning
confidence: 99%